In-vitro evaluation of antioxidant activity of Phaleria macrocarpa using different extraction process and determination of functional groups in the extract by FTIR (Fourier Transform Infrared Spectroscopy) - Anisya, Shifa Nur (Malaysian Institute of Chemistry, 2024)
P. macrocarpa is often known as “God’s crown” due to its great nutritional importance for human health. P. macrocarpa fruit can delay and avoid oxidative cell damage in the body by its antioxidant properties. In the meantime, there is still lacking yield, antioxidant activity, and functional properties of P. macrocarpa fruit in the sonication method using water and ethanol. So, this study aims to compare P. macrocarpa fruit yield, and antioxidant properties and to identify its functional group. Crude ethanol extract and water extract of P. macrocarpa fruit have been studied for Ferric Reducing Antioxidant Power (FRAP) and 2,2- Diphenyl-1- Picrylhydrazyl (DPPH) antioxidant activities against Ascorbic acid as a standard. The study also determined the functional group using FTIR (Fourier Transform Infrared Spectroscopy) assay. The most effective P. macrocarpa fruit yield was obtained in the water extract compared to the ethanol extract. In addition, the ethanol extract showed a higher FRAP (54.285±1.139 mgAAE/g) effect than the water extract. Besides, the DPPH activity of ethanol extract (46.113±1.535 µg/mL) was higher than water extract (59.406±2.089 µg/mL) and lower than standard Ascorbic acid (8.287±0.125 µg/mL). Moreover, some functional groups such as -OH, aliphatic CH, aromatic CH, aromatic C=C and C=N were also identified in both P. macrocarpa fruit extracts. The results confirmed that the sonication method using ethanol and water could influence the yield of P. macrocarpa fruit extracts as well as antioxidant activities with different functional groups.